2022
DOI: 10.3164/jcbn.22-43
|View full text |Cite
|
Sign up to set email alerts
|

Iron as spirit of life to share under monopoly

Abstract: Any independent life requires iron to survive. Whereas iron deficiency causes oxygen insufficiency, excess iron is a risk for cancer, generating a double-edged sword. Iron metabolism is strictly regulated via specific systems, including iron-responsive element (IRE)/iron regulatory proteins (IRPs) and the corresponding ubiquitin ligase FBXL5. Here we briefly reflect the history of bioiron research and describe major recent advancements. Ferroptosis, a newly coined Fe(II)-dependent regulated necrosis, is provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…We have been working on iron-induced carcinogenesis for decades. Among them, repeated intraperitoneal injections of ferric nitrilotriacetate (Fe-NTA) induces renal cell carcinoma (RCC) in a high incidence (60 ~ 90%) in male rats [9,12]. In this model, renal tubular necrosis is observed as early as 30 min in the proximal tubular cells with various lipid peroxidation products [43][44][45][46], which are the observation of our own in the 1980's and 1990's.…”
Section: Ferroptosismentioning
confidence: 71%
See 4 more Smart Citations
“…We have been working on iron-induced carcinogenesis for decades. Among them, repeated intraperitoneal injections of ferric nitrilotriacetate (Fe-NTA) induces renal cell carcinoma (RCC) in a high incidence (60 ~ 90%) in male rats [9,12]. In this model, renal tubular necrosis is observed as early as 30 min in the proximal tubular cells with various lipid peroxidation products [43][44][45][46], which are the observation of our own in the 1980's and 1990's.…”
Section: Ferroptosismentioning
confidence: 71%
“…This is further based on our own observation and observation by other investigators that 1) excess iron in various human pathology is associated with higher risk for carcinogenesis [7][8][9]; 2) iron reduction by phlebotomy decreases the cancer risk and mortality in a human intervention study [10]; 3) repeated iron-catalyzed Fenton reaction causes aggressive cancer that is similar to human counterparts not only in macroscopic/microscopic morphology but also in genetic alterations [11,12]. These animal models include ferric nitrilotriacetate (Fe-NTA)-induced renal carcinogenesis [12][13][14][15] and asbestos-induced mesothelial carcinogenesis in rats [16][17][18][19]; 4) especially in the latter case, iron removal by iron chelating agent [20] or phlebotomy [21] can prevent mesothelial carcinogenesis to some extent. More detailed review on these topics are found elsewhere [9,12,22].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations